First observation of B[bar]s0→Ds2⁎+Xμ−ν[bar] decays - Aaij, Roel; Bachmann, Sebastian; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; Meißner, Marco; Uwer, Ulrich; et al. (Physics letters, 2011)
Using data collected with the LHCb detector in proton-proton collisions at a centre-of-mass energy of 7 TeV, the semileptonic decays B¯s0→Ds+Xμ−ν¯ and B¯s0→D0K+Xμ−ν¯ are detected. Two structures are observed in the D0K+ mass spectrum at masses consistent with the known Ds1(2536)+ and Ds2⁎(2573)+ mesons. The measured branching fractions relative to the total B¯s0 semileptonic rate are B(B¯s0→Ds2⁎+Xμ−ν¯)/B(B¯s0→Xμ−ν¯)=(3.3±1.0±0.4)%, and B(B¯s0→Ds1+Xμ−ν¯)/B(B¯s0→Xμ−ν¯)=(5.4±1.2±0.5)%, where the first uncertainty is statistical and the second is systematic. This is the first observation of the Ds2⁎+ state in B¯s0 decays; we also measure its mass and width.